On the first Bulgarian music textbooks and collections with children‘s and school songs - Draganova, Rossitsa (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
The text is devoted to the musical-pedagogical practice in the Bulgarian school in the period immediately after the Liberation. The first Bulgarian textbooks on music and collections of children‘s and school songs are presented, used in the conditions of the intensely developing Bulgarian education and musical culture at that time. The report also discusses the problem of teacher training and the repertoire of the Bulgarian school, as well as the qualities and peculiarities of the collections of children‘s and school songs used in the educational practice at the very end of the 19th century.